2013
DOI: 10.11114/smc.v1i1.64
|View full text |Cite
|
Sign up to set email alerts
|

The Map is Not Which Territory?: Speculating on the Geo-Spatial Diffusion of Ideas in the Arab Spring of 2011

Abstract: The process by which social movements move through time and space can be understood as a process of innovation diffusion of memes or ideas. This process of diffusion may be traceable through computational linguistics and map geocoding of the linguistic memes employed by such movements. A Visualizing Information Space In Ontological Networks (VISION) method is described and illustrated with web-based search results of keywords relevant to Arab Spring. Using map algebra, and with the potential for using computat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
2
1

Relationship

2
7

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 101 publications
0
6
0
Order By: Relevance
“…For example, González‐Bailón et al's () study of the arousal, valence, and dominance codes of words used in online political discussions as predictors of political approval rates over time was interpreted in the framework of agenda‐setting theory (Hong Nga Nguyen & Gehrau, ), in which such memes both reflected, and primed, public agendas and may reflect the framing of media gatekeepers (Scheufele & Tewksbury, ). Research on the diffusion of the Arab Spring revolts suggested that despite the wide scale influences of social media and the internet, individual governments responded in various ways and through various media institutions in attempting to mitigate those influences, with varying degrees of effectiveness (Spitzberg, Tsou, An, Gupta, & Gawron, ). Research is beginning to identify the sources, for example, of attempts to machine‐manipulate social media campaigns by seeding memes (e.g., Tweets) to raise the profile of a particular issue or person (Ratkiewicz et al, ).…”
Section: The Societal Levelmentioning
confidence: 99%
“…For example, González‐Bailón et al's () study of the arousal, valence, and dominance codes of words used in online political discussions as predictors of political approval rates over time was interpreted in the framework of agenda‐setting theory (Hong Nga Nguyen & Gehrau, ), in which such memes both reflected, and primed, public agendas and may reflect the framing of media gatekeepers (Scheufele & Tewksbury, ). Research on the diffusion of the Arab Spring revolts suggested that despite the wide scale influences of social media and the internet, individual governments responded in various ways and through various media institutions in attempting to mitigate those influences, with varying degrees of effectiveness (Spitzberg, Tsou, An, Gupta, & Gawron, ). Research is beginning to identify the sources, for example, of attempts to machine‐manipulate social media campaigns by seeding memes (e.g., Tweets) to raise the profile of a particular issue or person (Ratkiewicz et al, ).…”
Section: The Societal Levelmentioning
confidence: 99%
“…As elsewhere, the Arab region has witnessed unprecedented developments in information communication technologies (ICTs). New technologies, according to Spitzberg et al, have “changed the velocity, the capacity, and the efficiency of communication” (: 110). By 2014, the International Telecommunication Union accounted for about 82% of schools in Tunisia, for instance, to have access to the Internet, as compared to 50% in Egypt and about 55% in Algeria .…”
Section: Social Media In the Midst Of The Arab Spring Revolutionsmentioning
confidence: 99%
“…Kernel density estimation (KDE) is used to identify the hotspots of tweets. KDE has been used to map the distribution of social media data in many studies—e.g., [ 2 , 4 , 21 , 34 , 35 , 42 , 43 ]. KDE inputs x , y , z and outputs a map in raster format where each cell has a value representing the level of intensity.…”
Section: Data Analysis and Visualizationmentioning
confidence: 99%